Foreign Exchange Rate Fluctuations and their Effects on Trade in the Last Five Years (2018–2022) in Uganda - Kartin Baguma (Uganda Christian University, 2023)
The study aimed at examining the effect of foreign exchange rate fluctuations on trade in the last five years (2018-2022) in Uganda. The study was guided by objectives which included: establishing the current state of foreign exchange rate fluctuations on trade in Uganda from 2018-2022, examining the short and long run effects of foreign exchange rate fluctuations on trade in the last five years in Uganda and determining the key drivers behind the observed foreign exchange rate fluctuations in Uganda and their implications for the country’s trade competitiveness. The study used secondary data in order to achieve the stated research objective. The data was obtained from Uganda Bureau of Statistics and Bank of Uganda. Trade was analyzed with the foreign exchange rate fluctuations for the period of five years (2018-2022). The research findings based on extensive secondary data analysis in Uganda shed light on the intricate dynamics of foreign exchange rate fluctuations and their profound impact on trade and the economy from 2018 to 2022. These findings underscored the significance of a stable exchange rate for trade competitiveness and economic stability. While Uganda has made progress in managing its balance of payments, controlling inflation, and adjusting interest rates, persistent challenges such as forex market regulation, export performance, and the implications of an ambitious infrastructure program persist. Addressing these challenges effectively is imperative for Uganda to navigate foreign exchange rate fluctuations, enhance trade competitiveness, and promote long-term economic resilience. Finally, the study recommended a comprehensive strategy for Uganda to manage foreign exchange rate fluctuations effectively. This included diversifying exports and adding value to reduce reliance on volatile commodities, strengthening forex market regulation, maintaining stable monetary policies, and carefully managing infrastructure projects. Improving export quality, monitoring the current account balance, reviewing forex market regulations, fostering collaboration, and attracting foreign investment are also key. Prudent infrastructure investment, exploring forex-friendly financing, and avoiding undue pressure on forex reserves are essential considerations.
This is a dissertation.